The Evolution of Advanced Prosthodontic Care: A 30-Year Patient Report - Thomas J. Balshi, DDS, FACP;1 Stephen F. Balshi, MBE;2 (Journal of Prosthodontics, 2007)
This clinical report demonstrates the history of a patient with progressive periodontal deterioration and illustrates how prosthodontic treatment has evolved over time.